The role of immunomodulators on intestinal barrier homeostasis in experimental models. Issue 6 (December 2015) - Andrade, Maria Emília Rabelo; Araújo, Raquel Silva; de Barros, Patrícia Aparecida Vieira; Soares, Anne Danieli Nascimento; Abrantes, Fernanda Alves; Generoso, Simone de Vasconcelos; Fernandes, Simone Odília Antunes; Cardoso, Valbert Nascimento
Summary: The intestinal epithelium is composed of specialized epithelial cells that form a physical and biochemical barrier to commensal and pathogenic microorganisms. However, dysregulation of the epithelial barrier function can lead to increased intestinal permeability and bacterial translocation across the intestinal mucosa, which contributes to local and systemic immune activation. The increase in these parameters is associated with inflammatory bowel disease, physical exercise under heat stress, intestinal obstruction, ischemia, and mucositis, among other conditions. Lately, there has been growing interest in immunomodulatory nutrients and probiotics that can regulate host immune and inflammatory responses and possibly restore the intestinal barrier. Immunomodulators such as amino acids (glutamine, arginine, tryptophan, and citrulline), fatty acids (short-chain and omega-3 fatty acids and conjugated linoleic acids), and probiotics ( Bifidobacterium, Saccharomyces, and Lactobacillus ) have been reported in the literature. Here, we review the critical roles of immunomodulatory nutrients in supporting gut barrier integrity and function.